Being Mapuche in the University: Entry Conditions to the Initial Teacher Training, La Araucanía - Ortiz-Velosa, Eliana Marcela (2019)
This article problematizes social factors that affect the entry to and continuity in higher education of indigenous students who belong to involuntary minority cultures. We advocate the thesis that Mapuche students face personal and social problems that become intercultural tensions whose origin, among other factors, is related to their life before they enter the university. The article aims to describe demographic and academic characteristics, as well as origins, that are particular to Mapuche students of the Education Faculty of Universidad Católica de Temuco. The methodology used was a descriptive statistic analysis of the database of the university. The analysis allowed to draft a demographic profile based on the territorial identities of the students. It also allowed the triangulation of the academic entry conditions, reflected in the students’ average high school grades (NEM), their origin, and their preferences for professional training in the educational area. We conclude that knowing this information, demographic and academic conditions, and preferences in professional training, will allow us to progress in managing strategies and guidelines of action to support students in the process of insertion in the university life.